Mengembangkan Sportivitas Melalui Permainan Modifikasi Hot (Hoki Tiup) - Sufiati, Vivi; Damayanti, Dwinda (Institut Agama Islam Negeri Ponorogo, 2021)
This study aims to determine the development of sportsmanship in children through a modified game of HOT (Hoki Tiup) during the pandemic. The research was conducted at Rumah Belajar All Kids. The research subjects were selected by purposive sampling, namely 4 children aged 5-6 years who did limited face-to-face learning. This research is a qualitative research with a case study approach. Methods of data collection used interviews, observation, and document study. The data analysis was used the data reduction stage, data presentation and conclusion drawing. The results of this study indicate that sportsmanship develops from the aspects of respect, fairness, and acceptance of the results of the game. Respect is shown through natural expressions when experiencing victory or defeat. A fair attitude is marked by the child starting to obey the rules of the game when playing with all his friends.The child receives the final result of the game.